Ius novum (Wyższa Szkoła Handlu i Prawa im. Ryszarda Łazarskiego w Warszawie, 2007)
The main editorial goal is to present opinions on the proposals of legislative changes, legal solutions passed, and the results of their retrospective verification. The scope of the journal is not limited to one or two branches of law but is a forum to exchange thoughts concerning law sensu largo. The thematic range of „Ius Novum" is broad and covers the history of law, political and legal doctrines, Roman law, civil law, criminal law, administrative law, business law, etc.